DESCRIPTION OF STUDENT'S REFRACTIVE THINKING IN VIEW OF PERSONALITY TYPES - Chumaedi Sugihandardji; Nurul Istiqomah; Ari Wardayani; Erni Widiyastuti; Gunawan Gunawan; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2023)
This study aims to describe the refractive thinking of class VIII B students of SMP Negeri 1 Sumbang. They are distributed in terms of thinking and feeling personality types. This type of research is qualitative research. The sample of this study was six students from class VIII B who were selected using a purposive sampling method. Data collection techniques are questionnaires, refractive thinking tests, interviews, and documentation. Data analysis techniques are divided into three stages: data reduction, data presentation, and conclusion. The results of this study indicate that students with the thinking personality type can gather information on the problem, link information in the issue with prior knowledge, propose solutions or alternative solutions to problems, eliminate solutions or alternative solutions to issues, carry out appropriate solving strategies and re-examine the solutions that have been obtained. Feeling personality type, students can gather information on the problem, relate the information in the issue with previous knowledge, and propose solutions or alternative solutions to problems